2012
DOI: 10.1673/031.012.1901
|View full text |Cite
|
Sign up to set email alerts
|

Gross Morphology and Histology of Head and Salivary Apparatus of the Predatory Bug,Rhynocoris marginatus

Abstract: Rhynocoris marginatus Fabricius (Hemiptera: Reduviidae) is an important biological control agent against more than 25 insect pests in India. For a better understanding of the feeding adaptation of this bug, the gross morphology and histology of its head and salivary apparatus were studied using both a light microscope and scanning electron microscope. The head is more or less elongate, mobile, and immersed into the eyes. R. marginatus has a three-segmented curved rostrum; the middle segment is longer than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
3
23
0
1
Order By: Relevance
“…Orcein (for proteins-DNA complexed), Feulgen reaction (specific to DNA) and C-Banding (for constitutive heterochromatin), which are specific for chromatin staining, showed a predominance of decondensed chromatin, as already described for salivary glands of other Hemiptera (laCoMBe, 1999;anHê & azereDo-oliVeira, 2008;serrão et al, 2008;kuMar & saHayaraj, 2012;De Castro et al, 2013;Martínez et al, 2014). These characteristics indicated increasing nuclear mass in relation to the cytoplasm and increasing metabolic activity (li et al, 2007), necessary to produce saliva.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Orcein (for proteins-DNA complexed), Feulgen reaction (specific to DNA) and C-Banding (for constitutive heterochromatin), which are specific for chromatin staining, showed a predominance of decondensed chromatin, as already described for salivary glands of other Hemiptera (laCoMBe, 1999;anHê & azereDo-oliVeira, 2008;serrão et al, 2008;kuMar & saHayaraj, 2012;De Castro et al, 2013;Martínez et al, 2014). These characteristics indicated increasing nuclear mass in relation to the cytoplasm and increasing metabolic activity (li et al, 2007), necessary to produce saliva.…”
Section: Discussionsupporting
confidence: 67%
“…Since fully active nucleoli are large (nanya & BiCuDo, 1995;CarMo-FonseCa et al, 2000), it can be suggested that this large nucleolar area was related with high cellular metabolism. Large nucleolar area was described for salivary glands of other Hemiptera (laCoMBe, 1999;anHê & azereDo-oliVeira, 2008;serrão et al, 2008;kuMar & saHayaraj, 2012;De Castro et al, 2013;Martínez et al, 2014). A previous study showed acid phosphatase activity in salivary gland cells of R. neglectus and R. prolixus.…”
Section: Discussionmentioning
confidence: 87%
“…The two lobes of the stink bug salivary gland are believed to produce watery saliva (ASG) and sheath saliva (PSG) (Kumar and Sahayaraj, 2012;Miles, 1972;Will et al, 2012). Watery saliva is involved with digestion of plant food and contains essential digestive enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the feeding adaptive features, reduviid predators have mandibular stylet tips with barbs or tooth or knifelike (Cohen 1996;Sahayaraj and Vinothkanna 2011;Kumar and Sahayaraj 2012), an organ usually used for predator. Though more than 96 % of reduviid predators are zoophagous, Harpactorinae species live in a specific relationship with certain plant species from which they obtain carbohydrates from food bodies, extrafloral nectar and hemipteran honeydew, or from sap by biting the plants (says Stoner et al 1975;Bérenger and Pluot-Sigwalt 1997;Tallamy et al 2004).…”
Section: Plant-associated Reduviidsmentioning
confidence: 99%